Fast Skeletal Muscle Troponin and Tropomyosin as a Dietary Source of Antidiabetic and Antihypertensive Bioactive Peptides: An In Silico Study - Barrero, Jorge Andrés; Barrero, María Alejandra; González Clavijo, Angélica María; Cruz, Claudia Marcela (Vitae, 2023)
Background: The nutraceutical properties of food hydrolysates rely on multiple biochemical interactions involving the modulation of enzymes and cellular receptors. Numerous bioactive peptides released from troponin and tropomyosin digestion have been identified. Their characterization has mostly been performed by hydrolysis catalyzed by proteases unrelated to the human digestive system. Objective: This study aimed to determine the bioactive profile of beef, pork, and chicken meat by analyzing the frequency and pharmacokinetics of biopeptides released from troponin and tropomyosin. Methods: In silico digestion and biopeptide release frequency were studied by three parameters; bioactive fragments release frequency (AE), frequency percentage (W), and mean occurrence (AS), all stated on the BIOPEP-UWM platform. Further on, hydrolysis end-products were screened based on gastrointestinal-absorption probability and pharmacokinetic profiling performed on SwissADME, SwissTargetPrediction, and ADME/Tlab bioinformatics web tools. Statistical analyses were performed using a one-way ANOVA test. Results: Dipeptidyl peptidase-IV (DPP-IV) and angiotensin-converting enzyme (ACE) inhibiting biopeptides exhibited the highest release frequency. Moreover, W and AS parameters showed no significant difference (p>0.05) between the myofibrillar isoforms assessed. Seven biopeptides were classified as highly absorbable and reported optimal drug-likeness compliance. Although biopeptides hold good pharmacokinetic properties, the therapeutic potency of biopeptides has been shown to be lower than those of DPP-IV and ACE-inhibiting drugs. Conclusions: Troponin and tropomyosin are rich dietary sources of bioactive peptides, mainly DPP-IV and ACE inhibitors. Digestion end-products are mainly dipeptides with optimal pharmacokinetic and drug-like properties, suggesting a potential therapeutic application in hypertensive and hyperglycemic disorders.